A Research Agenda for Gender and Substance Use Disorders in the Emergency Department. (1st December 2014) - Choo, Esther K.; Beauchamp, Gillian; Beaudoin, Francesca L.; Bernstein, Edward; Bernstein, Judith; Bernstein, Steven L.; Broderick, Kerryann B.; Cannon, Robert D.; D'Onofrio, Gail; Greenberg, Marna R.; Hawk, Kathryn; Hayes, Rashelle B.; et al.
Abstract For many years, gender differences have been recognized as important factors in the etiology, pathophysiology, comorbidities, and treatment needs and outcomes associated with the use of alcohol, drugs, and tobacco. However, little is known about how these gender‐specific differences affect ED utilization; responses to ED‐based interventions; needs for substance use treatment and barriers to accessing care among patients in the ED; or outcomes after an alcohol‐, drug‐, or tobacco‐related visit. As part of the 2014 Academic Emergency Medicine consensus conference on "Gender‐Specific Research in Emergency Care: Investigate, Understand and Translate How Gender Affects Patient Outcomes, " a breakout group convened to generate a research agenda on priority questions related to substance use disorders.